The contractual relationship between the involved parties in Takaful industry in light of Islamic law - Ibrahim, Ahmad Basri (s.n, 2012)
The concept of Takaful (Islamic insurance) was first introduced in Malaysia in 1985 when the first Takaful operator was established to fulfill the need of the general public to be protected based on the Islamic principle. This research highlight the contractual relationship which can be divided into three major relations that involve between three parties Takaful company, Takaful participants and takaful fund